Recommendations for Investigating the Cross-Category Effect Among Hispanic and Latino Populations. (March 2023) - Rennels, Jennifer L.
Individuals who are Hispanic or Latino make up a substantial portion of the U.S. and world population yet are vastly underrepresented as both participants and stimuli in the face-perception literature. Perceiving and recognizing faces are critical components of everyday social interactions, but cross-category effects (difficulty recognizing faces from other races or ethnicities) can hinder social interactions. Cross-category effects are the most commonly studied face-perception topic with these ethnic groups, but this empirical knowledge should be expanded via culturally relevant considerations. In this article, I describe (a) errors individuals display when categorizing target faces, (b) how social status influences identity and cross-category effects, (c) the potential impact of flexible and heterogeneous social identities on face processing, (d) a critical need for more developmental research, and (e) methodological expansions and generalizability concerns. Thus, I propose important directions for future studies to address these issues and advance knowledge in the field.